Prevention of Major Dental Diseases in Preschool Children (Eurasian Medical Research Periodical, 2022)
Prevention of dental diseases is a prevention of the occurrence and development of diseases of the oral cavity. This direction should be a priority in modern dentistry. The experience of many countries shows that a simple quantitative increase in the staff, funding and material support of the dental service is not enough to change the current situation in the prevalence and intensity of dental caries and periodontal disease. World dental practice has convincingly proved that the implementation of prevention programs leads to a sharp decrease in the intensity of dental caries and periodontal disease, a significant decrease in cases of tooth loss in childhood and an increase in the number of children and adolescents with intact teeth. An important argument is that the cost of preventive methods, on average, is 20 times lower than the cost of treating dental diseases that have already occurredTeeth